2023
DOI: 10.3390/agronomy13020544
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Industrial Compost in Soilless Cultivation Modulates the Vitamin C Content and Phytochemical Markers of Plant Stress in Rocket Salad (Diplotaxis tenuifolia (L.) DC.)

Abstract: Rocket salad is an important vegetable for the ready-to-eat sector, normally cultivated under greenhouse conditions, either in soil or soilless systems. In the latter case, as well as in the nurseries, its cultivation is usually carried out by using peat as a growing medium—a non-renewable substrate—for which it is urgent to find a replacement. Similarly to peat, compost may be used as a growing medium; however, depending on its origin, the chemical and physical characteristics may not bet suitable for plants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…The observed increase in ascorbic acid agrees with previous results in which the ascorbic acid concentration was higher with compost in strawberries, peppers, and rocket salad [82], and in which a cultivar-specific response to lettuce in closed soilless cultivation was found [83]. Ascorbic acid is a potent biological antioxidant involved in both pathogen defense mechanisms and growth modulation via phytohormone signaling [36].…”
Section: Effect Of Growing Medium On the Leaf Antioxidant Compounds A...supporting
confidence: 91%
See 1 more Smart Citation
“…The observed increase in ascorbic acid agrees with previous results in which the ascorbic acid concentration was higher with compost in strawberries, peppers, and rocket salad [82], and in which a cultivar-specific response to lettuce in closed soilless cultivation was found [83]. Ascorbic acid is a potent biological antioxidant involved in both pathogen defense mechanisms and growth modulation via phytohormone signaling [36].…”
Section: Effect Of Growing Medium On the Leaf Antioxidant Compounds A...supporting
confidence: 91%
“…In the present work, the polyphenol content was in the range of 367.1 to 551.4 mg GAE 100 g −1 f.w., resulting in slightly higher than the ones found by Gimenez et al [73] and Martinez et al [47], taking into account that the average dry matter (d.w.) value found in our samples was 15%. Indeed, these authors reported an average value, respectively, of The observed increase in ascorbic acid agrees with previous results in which the ascorbic acid concentration was higher with compost in strawberries, peppers, and rocket salad [82], and in which a cultivar-specific response to lettuce in closed soilless cultivation was found [83].…”
Section: Effect Of Growing Medium On the Leaf Antioxidant Compounds A...supporting
confidence: 90%
“…Significant differences in nitrate concentration were found between wild rocket leaves harvested from plants grown in different growing media, with those cultivated in compost having the highest concentrations (Figure 4a). This is not surprising, as the content of total N in compost was four-fold that in peat [25]. The nitrogen in the compost was hence (at least partly) released into the drainage nutrient solution which had, indeed, a nitrate concentration three to four times higher than the drainage obtained from peat (data not shown).…”
Section: Nitrate Contentmentioning
confidence: 82%
“…cv. Apollo]) are described by Signore et al [25]. Briefly, plants were cultivated in metal gutters filled with peat or an agro-industrial compost as growing media.…”
Section: Plant Materials and Growing Conditions For Main Crop (Wild R...mentioning
confidence: 99%
“…In order to provide a comprehensive understanding of the system, we will apply it to an urban farming research project and will showcase its adaption to this system. The urban farming setting has the goal of optimising the use of hydroponic cascade systems in urban agriculture to crop autochthonous vegetables [34], for example, by diminishing the nutrient load closing nutrient cycles and using compost and its extracts with salt‐tolerant vegetables to qualify the nutritional implications of cascade systems, whilst using friendly packaging for Km0 distribution [35]. Next sections explain the three layers in detail.…”
Section: An Orchestrated Innovation System In Agritechmentioning
confidence: 99%